Enhancement of Magnetic Properties and Magnetocaloric Effects for Mn0.975Fe0.975P0.5Si0.5 Alloys by Optimizing Quenching Temperature. Issue 5 (17th May 2022) - Zheng, Zhigang; Wang, Hongyu; Li, Chengfeng; Chen, Xinglin; Zeng, Dechang; Yuan, Shengfu
Abstract : The effect of quenching temperature on phase structure and magnetocaloric properties of the Mn0.975 Fe0.975 P0.5 Si0.5 alloys are systematically studied by X‐ray diffraction, scanning electron microscope, differential scanning calorimetry, and vibrating sample magnetometer. The Mn0.975 Fe0.975 P0.5 Si0.5 alloys quenched at 1323, 1073, 873, and 673 K are all crystallized in the hexagonal Fe2 P‐type phase and the phase fraction of the Fe2 P phase increases with the decreases of quenching temperature. As the quenching temperature decreases from 1323 to 673 K, the crystal lattice of alloys expands and the atoms' occupation is more ordered, while the saturation magnetic moment increases from 3.71 to 4.10 μB  f.u. − 1 The values of thermal hysteresis increase linearly from 30 to 41 K when the quenching temperature is down to 673 K. This enhancement of the first‐order magnetic transition (FOMT) yields the maximum value of magnetic entropy change at 5 T increasing by 36%. To obtain excellent comprehensive properties for (Mn, Fe)2 (P, Si) alloys, the methods of doping B element in the Mn0.975 Fe0.975 P0.5 Si0.5 alloy are employed to tune the magnetocaloric properties. The results provide insights and systematic understanding into the effect of quenching temperature on the magnetocaloric properties of (Mn, Fe)2 (P, Si)‐based alloys. Abstract : The magnetocaloric properties of Mn0.975 Fe0.975 P0.5 Si0.5 alloy can be tuned by the method of low‐temperature quenching. With quenching temperature decreasing from 1323 to 673 K, the improving ferromagnetic interactions between the magnetic atoms make the magnetic moment and entropy change increase by 11% and 36%, respectively.